Bridging communication gap: overcoming age-related differences between the young adults and the elderly / Nur Asyikeen Kamarudin, Fazlinda Hamzah and Shafinar Ismail - Kamarudin, Nur Asyikeen; Hamzah, Fazlinda; Ismail, Shafinar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Communication is the act of exchanging meaning among entities through verbal or nonverbal means. However, communication breakdown may appear due to age-related differences between the young adults and the elderly. This is because during the process of aging, communication skills change subtly due to physical health and cognitive decline. Hence, there is a need to understand how to overcome these communication issues that could potentially create a more complex dynamic communication. Therefore, the purpose of this study was to explore the themes that construct young people’ understanding of effective communication within the older and young adult dyad. This study used a qualitative approach through a content analysis from an open-ended question in order to determine strategies used by the young adults when interacting with the older people. The qualitative data were thematically analysed and specific facets that contribute to the understanding of age-related differences are developed. The result indicates that speaking slowly, clearly and loudly, using short, simple words and sentences as well as avoiding distractions play crucial roles in overcoming communication problems. This research concludes by considering steps taken to facilitate effective communication between the young adults and the elderly.